Periodic table in the style of spiral with radii (Heinrich Adolph Baumhauer, 1870) - Baumhauer, Heinrich Adolph; Mazurs, Edward G. (1870)
Graphic representation of the periodic table of chemical elements depicted as a spiral with eight radii. This table was originated by German chemist Heinrich Adolph Baumhauer (1848-1926) in 1870 and classified by chemist Edward G. Mazurs as Type IB2-4 in his seminal work Types of Graphic Representation of the Periodic System of Chemical Elements (1957). In this design, the elements of subgroups "a" are placed on the radii and the elements of subgroups "b" are placed into the spaces between the radii. This illustration appears as Figure 29 on page 108 of Mazurs' 1957 publication.
Keywords: Scientific illustration; Periodic table of the elements; Periodic law; Chemical elements